2023
DOI: 10.3390/biology12060797
|View full text |Cite
|
Sign up to set email alerts
|

New Perspectives on the Role of Nuclear Proteases in Cell Death Pathways

Abstract: Multiple factors can trigger cell death via various pathways, and nuclear proteases have emerged as essential regulators of these processes. While certain nuclear proteases have been extensively studied and their mechanisms of action are well understood, others remain poorly characterized. Regulation of nuclear protease activity is a promising therapeutic strategy that could selectively induce favorable cell death pathways in specific tissues or organs. Thus, by understanding the roles of newly discovered or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 127 publications
0
1
0
Order By: Relevance
“…As a result of this phenomenon, recent studies have indicated that cathepsins can also translocate in the nucleus [95][96][97]. Interestingly, their activity within the nucleus appears to increase during apoptosis, even though more investigations are necessary to unveil the mechanisms underlying these phenomena [98]. Despite the role of ROS as a lysosome-permeabilizing agent, treatment of murine hepatoma cells with inhibitors of cathepsins L, B, and D did not prevent Bid activation after treatment with N-aspartyl chlorin e6 (NPe6) photosensitizer nanoparticles and subsequent irradiation [87].…”
Section: Interplay Between Ros and Cathepsins In Apoptosismentioning
confidence: 99%
“…As a result of this phenomenon, recent studies have indicated that cathepsins can also translocate in the nucleus [95][96][97]. Interestingly, their activity within the nucleus appears to increase during apoptosis, even though more investigations are necessary to unveil the mechanisms underlying these phenomena [98]. Despite the role of ROS as a lysosome-permeabilizing agent, treatment of murine hepatoma cells with inhibitors of cathepsins L, B, and D did not prevent Bid activation after treatment with N-aspartyl chlorin e6 (NPe6) photosensitizer nanoparticles and subsequent irradiation [87].…”
Section: Interplay Between Ros and Cathepsins In Apoptosismentioning
confidence: 99%